PENGARUH MINAT BELAJAR SISWA TERHADAP HASIL BELAJAR MATA PELAJARAN MATEMATIKA - Muhammad Agil Nugroho; Tatang Muhajang; Sandi Budiana (Universitas Pakuan, 2020)
INFLUENCE OF STUDENT LEARNING INTEREST IN RESULTS OF MATHEMATICS LEARNING OUTCOMESThe purpose of this study was to determine the effect of interest in learning on student learning outcomes. This research is a quantitative study with a causal study method on learning interest as an independent variable and learning outcomes as a dependent variable. The object of this research is the VA class and VB Kopo 01 Public Elementary School, Cisarua District, Bogor Regency Odd Semester Academic Year 2019/2020 totaling 98 with a sample of 50 respondents. The data of this study were obtained by using a Likert scale questionnaire for learning interest variables and using test questions for learning outcome variables. The results showed that there was a positive and significant influence between learning interests on learning outcomes. This is based on statistical analysis that produces a coefficient of determination (rxy) of 0.369 and in the pattern of the problem becomes Ŷ = -17.14 + (0.75x) which means the level of influence is classified as strong and is obtained tcount of 33.28 greater than ttable with a level significant 0.05 of 4.04, which means significant. Based on these results, it can be concluded that there is a positive and significant influence between learning interests on student learning outcomes.